2022
DOI: 10.1111/and.14372
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on blood pressure, lipid metabolism and erythrocytosis during and after androgen abuse

Abstract: The abuse of androgens, or anabolic androgenic steroids, is not uncommon among amateur strength athletes. Androgens entail testosterone, synthetic derivatives such as nandrolone and trenbolone, and the nonsteroidal selective androgen receptor modulators (SARMs). The term anabolic androgenic steroids is oxymoronic as there is no genuine distinction between anabolic and androgenic effects. Androgen abuse is defined as the use of androgens without a prescription, usually for the enhancement of muscle mass. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The recent Health risks of Anabolic Androgenic steRoid use by maLE aMateur athletes (HAARLEM) study examined male AAS users in a gym and reported that one cycle of AAS is associated with unfavorable cardiac function, blood lipid profile, and various other risk factors [ 20 , 21 ]. Though insightful, these studies lack a control group of non-AAS users [ 22 ].…”
Section: The Role Of Anabolic Androgenic Steroidsmentioning
confidence: 99%
“…The recent Health risks of Anabolic Androgenic steRoid use by maLE aMateur athletes (HAARLEM) study examined male AAS users in a gym and reported that one cycle of AAS is associated with unfavorable cardiac function, blood lipid profile, and various other risk factors [ 20 , 21 ]. Though insightful, these studies lack a control group of non-AAS users [ 22 ].…”
Section: The Role Of Anabolic Androgenic Steroidsmentioning
confidence: 99%
“…Measurements took place before, during and twice after the cycle. Health effects were divided into several categories: positive and negative adverse effects reported by the subjects, the results of kidney and liver biochemistry in blood, and the outcome of psychological questionnaires [4 ▪ ]; the disruption and recovery of endogenous testosterone production and spermatogenesis [5 ▪ ]; the change of cardiovascular parameters during androgen abuse, such as blood pressure, lipid metabolism and erythrocytosis [6 ▪ ]; and change of cardiac structure and function as evaluated with 3D echocardiography [7].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In the last 2−3 years several publications reported data from the HAARLEM study [3,4 ▪ –6 ▪ ,7], which is an acronym for health risks of anabolic androgenic steroid use by male amateur athletes. This cohort study takes precedence over much of the existing literature in this field due to its prospective design and relatively large size.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive and extended analytical retrospectivity for AASs have been subject of continued research, but also advanced means facilitating the differentiation of natural and endogenously produced steroids from synthetic substances as well as enhancing the understanding of metabolic pathways depending on drug amounts or application routes. 102 In the light of the considerable health risks associated with AASs, both physically [38][39][40][41][42][43] and psychologically, [44][45][46] detection and containment in recreational as well as elite sport remains critical. 103 Here, the utility of luteinizing hormone (LH) was revisited and reported to represent a sensitive marker for current androgen abuse, 47 which, in concert with established targeted testing approaches, can contribute further insights into the prevalence and misuse of steroidal substances.…”
Section: Anabolic Agentsmentioning
confidence: 99%